FAKTOR-FAKTOR YANG MEMPENGARUHI OUT FLOW PEREDARAN UANG RUPIAH TERHADAP PDRB DI PROVINSI SULAWESI SELATAN - Andi Muammar Qkhadafi (Delilah Tinggi Ilmu Ekonomi Jambatan Bulan, 2020)
This study aims to analyze the relationship between interest rates and inflows on the outflow money circulation in South Sulawesi, and to analyze the relationship between the Rupiah currency outflow and PDRB in South Sulawesi. The analytical tools used in this study is multiple linear analysis and simple linear analysis. The results showed that the inflow has a positive and significant effect on the money circulation outflow in South Sulawesi, the interest rate has a negative and insignificant effect on the money circulation outflow. Meanwhile, the money circulation outflow has a positive and significant effect on GRDP in South Sulawesi